Desain Pembelajaran Persamaan Diferensial melalui Pendekatan Kontekstual - Rita Pramujiyanti Khotimah; Masduki Masduki (Jurnal VARIDIKA, 2015)
Differential equity is one of the applied subjects needed to solve the problem in real situation, not only in Mathematics but also in engineering, biology, physics, chemistry, medics, psychology economy and others. However, the existing approach for teaching differential equity tends to be procedural. For this reason, the class of differential equity becomes not meaningful for students. Contextual teaching is one of the approach focuses on the students’ participation and process to find relation between material taught and real life. Through self discovery, it is expected that students experience meaningful learning. This research is the developing stage research by using contextual approach. The activities of students in contextual learning are elaborated in this research. The research aims at finding meaningful learning is not limited for procedural and analysis.